Analisis Pemahaman Siswa Kelas 10 MAS Alwashliyah Kedai Sianam pada Materi Konsep Ekosistem - Faisal, Muhammad; Phonna, Niea Zahara; Mardiah, Ros; Lestari, Dinda; Mahyuni, Risdah; Rahayu, Widya (Education Achievement: Journal of Science and Research, 2025)
Ecosystem is a discussion study in biology material that discusses the relationship between living things and their environment. The ecosystem includes a very large discussion and is divided into two factors, namely biotic factors and abiotic factors. Understanding the ecosystem is very important for all individuals to know, in order to provide a symbiosis of mutualism between each other, because the ecosystem is also a reciprocal relationship between living things and their environment. The purpose of this study is to analyze the understanding of 10th grade students of Mas Alwashliyah regarding the concept of ecosystems. The research method carried out was by distributing a form or questionnaire to 21 students in class X, and analyzed by qualitative methods. The results of the research obtained were the results of students' answers that answered the correct questions on average 94.75%, while the average answer of students who answered incorrectly was 5.25%. And the average of the student score is 94.76%.